Estimation of population structure, growth and condition of Parastromateus niger in the Bay of Bengal: suggestions for catchable sizes - Husna, Asmaul; Mondol, Md. Rashedul Kabir; Hasan, Md Rabiul; Hossain, Md. Yeamin (Acta Biologica Szegediensis, 2022)
Black pomfret (Parastromateus niger) is one of the major commercial species of pomfret fishery in Bangladesh. This study illustrates the population structure (Length Frequency Distribution, LFD), relationship between length and weight (LWR), relationships between length and length (LLRs), Fulton’s condition factor (KF) and relative weight (WR) of P. niger in the Bay of Bengal (BoB). A total of 225 P. niger were collected from the four locations during January to December 2020. LFD analysis indicates three length classes 21-27 cm, 30-32 cm and 35-37 cm, respectively. This species showed isometric growth pattern (b = 2.981) that indicates that the size and weight increases proportionally and the surrounding habitat provides favourable environment for the growth. LWR between TL and BW were highly correlated (r² = 0.951). LLRs also showed significant correlation between TL and SL (r² = 0.845) and TL and FL (r² = 0.861). The mean value of KF was found as 1.60 which indicates that the BoB provides healthy environment for this species. The mean value of WR (101.09) indicates that the relationship between prey and predator was in balanced condition. This study suggests optimum catchable length for P. niger at 27 cm. Therefore, these findings could provide important information to design effective conservation and management planning for this species.